Improving Decision Making Through Management Accounting : Practical and Theoretical Perspectives - Muhammad Ihsan Rangkuti (International Journal of Economics, Management and Accounting, 2024)
This research aims to analyze the role of management accounting in decision making and improving company performance, with a focus on the application of main techniques such as Cost-Volume-Profit (CVP) Analysis, Activity-Based Costing (ABC), and Balanced Scorecard (BSC). Through a qualitative approach with in-depth interviews and case studies on several companies, this research found that management accounting techniques contribute significantly to optimizing costs, increasing operational efficiency, and planning long-term strategies. The use of CVP Analysis helps companies plan more profitable product costs and prices, while ABC provides more accurate cost allocation for each activity in the value chain. On the other hand, BSC helps companies to assess performance as a whole, not only from a financial perspective, but also from non-financial aspects such as customer satisfaction and service quality. However, this research also identified several challenges, including limited resources, insufficient understanding of these techniques, and resistance to change within organizations. Limitations in the research sample and observation time are also factors that need to be considered. Overall, this research confirms the importance of implementing management accounting in improving company performance, but also shows that internal and external factors need to be considered in its implementation.